Peningkatan Pengelolaan Sarana dan Prasarana Pendidikan untuk Meningkatkan Kualitas Pembelajaran di SDN 106840 Kampung Benar - Cut Nurul Haniyah; Della Arsita Sari; Nila Riana Harahap; Nurul Zahara Bancin; Muhammad Jailani (Tarbiatuna: Journal of Islamic Education Studies, 2024)
Facilities management is very important because well-maintained and well-utilized educational institutions can be achieved thanks to these steps. School administrators, especially school principals, must be able to be responsible for the facilities and infrastructure they own. And the school must be able to maintain and maintain existing school facilities. Therefore, students can learn as effectively and efficiently as possible at school if adequate resources are available. Therefore, facility management needs to be emphasized even more in educational institutions such as schools. And there must be a party who is responsible for managing these resources. School administration can plan and monitor what facilities are needed in their buildings by monitoring the maintenance of existing facilities. If all management strategies go according to plan, it will have a positive impact on students' ability to learn from teachers and achieve educational goals efficiently and effectively. Therefore, education administrators, both government officials, school principals, teachers or other school staff and the general public must work together to improve educational standards so that they are in line with needs. era.